Marketing Channels for Horticultural Produce in Kenya – A Mapping of Channels Currently in Use by Farmers - Rutto, David K. L.; Omami, Elizabeth N. (International Journal of Research in Interdisciplinary Studies, 2025)
Horticultural produce can be sold in the farm or marketed through local fresh markets; local processed markets, fresh export markets, or processed export markets. Kenya has agro-ecological conditions that favor horticultural products which have been or are being developed and produced to meet various demand in order to satisfy quantity and quality levels of consumers. The marketing structure depends on where horticultural produce is produced and consumed. The problem in horticultural produce marketing is non-defined and varied channels for a given produce thereby needing its map out. Given a diversified demand structure, the objective of study was to map existing channels used by farmers for produce to follow during marketing, so as to reach respective target groups or consumers. In this research primary data was obtained through field survey using questionnaires and interviews. Respondents were selected through stratified random sampling method and 100 horticulture vendors and sellers in 5 markets of Eldoret, Kitale, Kisumu, Nairobi and Nyeri and 5 HCDA and 5 MOA officers in the five counties. Secondary data obtained from varied sources (FPEAK, HCDA and MOA reports) were obtained, compared and analyzed to come up with marketing channels for fruits, vegetables and cut flowers. Data obtained was subjected to descriptive and qualitative on excel. Results indicated that farmers pass and dispose of their horticultural produce through various market outlets including; modern channels like supermarkets, online trading portals and exports as well as traditional channels including rural and urban wholesale or retail markets. It was concluded that marketing channels of horticultural produce are varied and diverse with urban, rural and supermarkets preferred. It was recommended that marketers use varied marketing channels depending on horticulture produce at their disposal to enhance horticultural product flow and reduce costs.